PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING SMART APPS CREATOR (SAC) BAGI KARYAWAN PENJUAL PADA TV BERBAYAR - Khasanah khasanah; Maulana Muhlas; Lisna Marwani (Akademika : Jurnal Teknologi Pendidikan, 2020)
This study aims to develop E-Learning learning media and test the validity of Android-based Smart Apss Creator (SAC) products for transvision sales employees in Jakarta. Using the Research and development method. The development step refers to the Bord & Gall development model. There are 10 steps in the development of Borg & Gall, but this research is limited to 9 steps, namely research and collection of initial information, planning the initial product format development of the initial trial, product revision, small scale field trial, product revision, scale field trial the size and revision of the final product. The population in this study were 10 employees of PT. Transvision Jakarta sellers. The research sample goes through 3 stages, namely the User-Test (one-to-one), the Small Group Test and the Field Test. This SAC software contains information about the history of the company, the company's vision and mission and the products of the Transvision Company. Product development after validation by 3 media experts and by 3 material experts get a score of> 83 which indicates that this application is feasible to be implemented. Try out the use in 3 stages, one-to-one evaluation with 84% results, Small Group evaluation 83% then 83% field evaluation which shows that the application of the development is feasible to use.